Evaluation of hospital managers' performance in Sari - Alimohammad Mosadeghrad; Ebrahim Jaafaripooyan; mahdi abbasi (Tehran University of Medical Sciences, 2018)
Background: The success of organizations depnds on their managers' performance. This study aimed to measure hospital managers' performance in the city of sari in 2017, Iran. Materials and Methods: About 294 top, middle and first-line managers working in the hospitals in Sari (including four public, two private and one social security hospital) particaipated in this descriptive and cross-sectional study. A valid and reliable questionnaire was used to assess managers' performance in eight functions including decision making, planning, organizing, coordinating, leadership, communication, budgeting and control. SPSS software, the 21st version, was used for data analysis. Results: The mean score of hospital managers' performance was 3.87 out of 5.  Managers scored high in organizing (4.12), leadership (4.06), and decision making (3.97) and low in budgeting (3.27), planning (3.83), and coordinating (3.84). Managers' performance was linked to their age, marital status, education level, and educational background. Those managers who worked in a position related to their educational background had better performance. Conclusion: Hospital managers rated their performance as good. Measuring managers' performance, determining their strengths and weaknesses and applying corrective actions are beneficial to the improvement of hospitals' performance.